2016
DOI: 10.1177/1715163516629156
|View full text |Cite
|
Sign up to set email alerts
|

Natural health product–drug interaction tool

Abstract: Ginger Ginkgo 41 42 44 46 49 Asian ginseng Author Contributions: A. Kutt coordinated the project and contributed to the overview, methods, results determination and writing the manuscript. L. Girard initiated the project, reviewed papers for inclusion, developed preliminary results, drafted the initial manuscript and reviewed the manuscript. C. Necyk reviewed papers, developed preliminary results and reviewed the manuscript. H. Boon, J. Barnes and P. Gardiner provided expert opinion, developed classification s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…12 There is also a risk of interactions between NHPs and prescription medications. [13][14][15] A recent study found that patients who take both prescription medications and NHPs, compared to those who only take prescription medications, were over 6 times more likely to experience an adverse event. 16 Consequently, a tool to identify NHP-drug interactions was developed to aid clinicians in assessing patients' risk and published in CPJ.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…12 There is also a risk of interactions between NHPs and prescription medications. [13][14][15] A recent study found that patients who take both prescription medications and NHPs, compared to those who only take prescription medications, were over 6 times more likely to experience an adverse event. 16 Consequently, a tool to identify NHP-drug interactions was developed to aid clinicians in assessing patients' risk and published in CPJ.…”
Section: Original Researchmentioning
confidence: 99%
“…16 Consequently, a tool to identify NHP-drug interactions was developed to aid clinicians in assessing patients' risk and published in CPJ. 15 Some respondents cited concern over television advertisements that communicate the Original research potential adverse effects of prescription drugs. However, there was no recognition that NHPs are not required to disclose potential adverse effects of therapy.…”
Section: Original Researchmentioning
confidence: 99%
“…Although the prevalence of self‐reported adverse events in our study was low (3%), patient safety is still a concern as patients may not associate experienced symptoms as adverse effects, and previous studies suggest that most patients do not feel comfortable reporting potential adverse events associated with s‐NHP use to healthcare providers (Ramos‐Remus & Raut, ; Walji et al, ). High‐quality clinical studies demonstrating efficacy and safety are lacking for most, if not all, s‐NHPs, and their adverse effect profiles and potential for drug interactions are not well known (Kolasinski, ; Kutt et al, ; Setty & Sigal, ).…”
Section: Discussionmentioning
confidence: 99%
“…Observed undesirable reactions can be due to the toxicity of herbal ingredients by themselves or the quality issues, such as improper processing methods, or contamination and adulteration with toxic substances or foreign matters (Shaw, 2010). In addition, relevant interactions with other drugs can occur, possibly resulting in adverse outcomes (Ben‐Arye et al, 2016; Fasinu, Bouic, & Rosenkranz, 2012; Kutt et al, 2016; Ramos‐Esquivel, Viquez‐Jaikel, & Fernandez, 2017; Tsai, Lin, Simon Pickard, Tsai, & Mahady, 2012). Cultural familiarity with traditional herbal medicine may bring about underestimation of risks of herbal medicinal products (Lam, 2001).…”
Section: Risk Assessmentmentioning
confidence: 99%